Online Shop Untuk Sistem Penunjang Keputusan Barang Paling Diminati Menggunakan Metode Apriori - Sularno Sularno; Zulfahmi Zulfahmi; Putri Anggraini (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2022)
Currently, competition in the business world is increasingly competitive and growing. Supported by technology that is growing rapidly, many online shops have sprung up which are better known as online shops. However, it is not uncommon for many small to medium-sized shops, especially those engaged in clothing, to not have a website to market their products. The marketing is only limited to the location of the store and cannot be widely marketed to other people. So that buyers find it difficult if they want to compare prices or see the goods sold at the store and CV. Dodoi Collection can see the items that buyers are most interested in using the a priori method. The purpose of this research is to build an online shop at CV. Dodoi Collection along with a decision-making system to determine the most desirable clothes using the a priori method and displaying the most popular items on the CV. Dodoi Collection so that the clothing production process is more efficient. The research was conducted directly in the field by using interview techniques, then by studying books, literature related to the problems discussed. After the data is collected, then the data is grouped and analyzed using the Unified Modeling Language (UML). The results of the analysis are applied to a phpmysql-based data processing information system application program. The methodology that guides the system development activities is the SDLC. The SDLC model used in this study is the WaterFall Model. The results of this study are expected to help companies to market their products more broadly by using an online shop and being able to display the most desirable products on the CV. Dodoi Collection